Augmentation of autologous bone graft by a combination of bone morphogenic protein and bisphosphonate increased both callus volume and strength - Bosemark, Per (Informa Healthcare, 2013)
BACKGROUND AND PURPOSE: Bone morphogenic proteins (BMPs) can be used in non-unions to replace autograft. BMPs induce osteoblasts and (less well known) also osteoclasts, which can in turn be controlled by a bisphosphonate. In the present study, our aim was to improve the biological effect of autologous bone graft by adding an anabolic BMP, with or without bisphosphonates, in an open-fracture model prone to non-union. METHODS: Rat femurs were osteotomized and fixed with an intramedullary K-wire. Autograft was placed at the osteotomy, mixed with either saline or BMP-7. After 2 weeks, the rats had a single injection of saline or of a bisphosphonate (zoledronate). The rats were killed after 6 weeks and the femurs were evaluated by radiography, micro-CT, histology, and 3-point bending test. RESULTS: All fractures healed. The callus volume was doubled in the BMP-treated femurs (p < 0.01) and increased almost 4-fold in the femurs treated with both BMP and systemic zoledronate (p < 0.01) compared to autograft. In mechanical testing, the autograft group reached approximately half the strength of the contralateral, non-osteotomized femur (p < 0.001). By adding BMP to the autograft, the strength was doubled (p < 0.001) and with both BMP and systemic zoledronate, the strength was increased 4-fold (p < 0.001) compared to autograft alone. INTERPRETATION: The combination of BMP and bisphosphonate as an adjunct to autograft is superior to autograft alone or combined with BMP. The combination may prove valuable in the treatment of non-unions.